Movement Restriction and Increased Surveillance as Efficient Measures to Control the Spread of Highly Pathogenic Avian Influenza in Backyard Productive Systems in Central Chile - Di Pillo, Francisca; Jimenez-Bluhm, Pedro; Baumberger, Cecilia; Marambio, Víctor; Galdames, Pablo; Monti, Gustavo; Schultz-Cherry, Stacey; Hamilton-West, Christopher (Frontiers in Veterinary Science, 2020)
During the last five years there has been an alarming number of reports of highly pathogenic avian influenza worldwide. However, little is known about the status of this disease in South America. Chile has been the only country in South America where an HPAI outbreak has occurred. This outbreak occurred in 2002 and was due to an H7N3 HPAI, where the most plausible hypothesis that explained the entrance of the disease to the country, had relation to migratory wild birds. Commercial poultry farms in Chile are highly integrated and have high biosecurity standards. On the other hand, poultry backyard production systems lack biosecurity measures and are widely distributed. Since 2002 outbreak, avian influenza viruses have been identified in wild birds and different animal species kept in backyard productive systems (BPS) in Chile. The aim of this study was to simulate the possible natural history of HPAI after its introduction to BPS in central Chile and to simulate different intervention strategies. To do so, the North American Animal Disease Spread Model version 3.3 was used. The results showed that a median of 11,299 BPS would be affected if HPAI spread among BPS in central Chile, representing 69% of the current amount of BPS existing in study zone. Movement restrictions, pre-emptive destruction, passive surveillance and combinations of the three, where the intervention strategies tested in the simulation model. From all the interventions simulated, movement restrictions together with increasing passive surveillance had the biggest effect, reducing the median number of infected BPS to 4,288. However, the model was formulated based on the contact rates described for BPS in the United States, which may have an impact on the described results. These results can guide the official veterinary services to consider potential mechanisms to control or prevent a HPAI emergency situation, nevertheless, further studies are needed to generate contact rates in the context of the Chilean situation.